An original dramaturgy about torture, from the South: 50 years of Torquemada, by Augusto Boal (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The article presents a reflective investigation of Torquemada (1971), a play by Augusto Boal, beyond modern/colonial conventions, to broaden the studies on the “dramaturgies of the South”. The objective is to situate such dramaturgy, understood as “forgotten history” (rarely commented/studied/enacted) and “current” (referring to chronic social problems faced in contemporary Latin America, such as torture by State agents). The text is organized into three moments: Boal beyond the Theater of the Oppressed; Torquemada in its content-form, presented as a “colonial wound”; the senses and meanings of torture in a decolonial reading of the (con)text. It is concluded that the historical relevance of the playwright in the fight against the Brazilian civil-military regime and the international recognition as the creator of the Theater of the Oppressed relegated his authorial work to the background and that Torquemada is a document-witness of dark times of the storm that befell Brazil.
Keywords: Augusto Boal; Torquemada; Theatrical dramaturgy; Colonial wound; Torture